A plataforma virtual Ecaths: articulações entre o ensino e aprendizagem de língua inglesa e as possibilidades de letramento digital - Ramos, Oriosvaldo de Couto (2017)
This research describes and analyzes a pedagogical experience developed at the Escola de Referência em Ensino Médio Padre Antônio Barbosa Júnior - EREMPABJ, involving the use of the Virtual Platform Ecaths as a support to face-to-face teaching in basic education. The main objective of this work is to describe the virtual environment of the Ecaths platform and the feasibility of its tools for the teaching and learning of the English language and the possibilities of building the digital literacy of the students. The theoretical framework used was based on the conceptions of Rapaport (2008); Holden (2009); Paiva (2012) and Carvalho and Braga (2012) for the teaching of the English Language; The literacy concepts of Soares (2002) and Kleiman (1995), digital literacy, Buzato, (2006), Coscarelli (2014, 2016,Kenski (2015), Lemos and Matos (2016); ICT in education, Matos and Rodrigues (2013), Moran (2000, 2013), Prensky (2001), Toktov (2003) among others. The reflection about the pedagogical possibilities adopted for the case study generated data and analyzes capable of contributing not only to the improvement of the studied discipline, but also to subsidize any other teacher who wishes to use the virtual environment of the Ecaths platform in other contexts of teaching and learning. In order to reach the objective, in the course of the research, written tests and questionnaires were carried out to generate the data. In presenting the data, we used a qualitative analysis combined with elements of quantitative analysis, complemented by the observations of the researcher-teacher. At the end, we see that the experience is closely related to the socio-interactionist theories that consider the interaction, be it with the subject or the object, a premise for effective learning of both the structural and functional aspects of the English language, as well as the enabling of digital literacy.